Framing Media Online Sumut Antara News terhadap Pemberitaan Musibah Banjir di Tapanuli Selatan Tahun 2025 - Diva, Rangga; Indra, Farhan (Jurnal Ragam Pengabdian, 2026)
Flood disasters frequently receive extensive media coverage because they have significant social impacts and influence public perceptions through news framing. This study aims to analyze how Sumut ANTARA News framed the flood disaster in South Tapanuli, examine the accuracy of the published information, and explore public perceptions of the news coverage. This qualitative study employed Robert N. Entman’s framing analysis model, consisting of define problems, diagnose causes, make moral judgment, and treatment recommendation. Data were collected through the analysis of six news articles published by Sumut ANTARA News between November 2025 and January 2026, interviews with ANTARA journalists and South Tapanuli residents, and documentation. The findings indicate that Sumut ANTARA News predominantly employed a Humanitarian and Recovery Frame, emphasizing the social impacts of the disaster, natural causes, humanitarian values, and post-disaster recovery efforts. The study also found that the news demonstrated a high level of accuracy through a rigorous journalistic verification process before publication. Furthermore, the public perceived the news positively, considering it factual, understandable, and consistent with actual conditions. These findings suggest that Sumut ANTARA News effectively combines accurate reporting with constructive framing in disaster coverage.